Morphological, phytochemical, and molecular profiling of bamboo species (Bambuseae) growing in various ecosystems of Cagayan Province, Luzon, Philippines - JEFF M. OPEÑA; REYMELYN A. BUMANGLAG; VENZ MAR T. CABANG (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Opeña JM, Bumanglag RA, Cabang VMT. 2023. Morphological, phytochemical, and molecular profiling of bamboo species (Bambuseae) growing in various ecosystems of Cagayan Province, Luzon, Philippines. Biodiversitas 24: 4342-4358. The characterization of bamboo species posed advantages to the bamboo industry’s development in the Philippines. This study aimed to provide baseline information on the environmental and biological profiles of bamboo species in Cagayan Province, Philippines. Study sites were visited for bamboo morphological characterization using character states. Leaves were collected for qualitative phytochemical screening of 10 secondary metabolites and DNA sequencing using the rbcL plastid gene. The 28 accessions of Bambusa, Dendrocalamus, Dinochloa, Gigantochloa, Guadua, Melocanna, Phyllostachys, Schizostachyum, and Thyrsostachys were characterized and these bamboos were growing in forests, coastal or sparsely vegetated lands, urban, freshwater, grasslands, and agricultural ecosystems. Bamboo species distinctiveness’ was described through identification keys on growth habit, culm internode, nodal structure, young shoot, and flowering incidence. The bamboos contain coumarins, saponins, steroids, and terpenoids, while quinones are absent. DNA sequencing using rbcL was effective in the identification of Bambusa vulgaris species and unknown bamboo at the species level. Dendrocalamus, Guadua, Melocanna, and Schizostachyum species were successfully identified by rbcL at the genus level. Most of the species were identified as Dendrocalamus species with rbcL. The findings provide valuable information on species identification and certification for asexual propagation, genetic conservation, phytochemical extraction, and utilization for health.